Fac-simile del Concerto funebre di Antonio Vivaldi - Vivaldi, Antonio 1678-1741; Bruers, A. (Siena Ticci, 1947)
The evocative Concerto funebre, RV579, was probably written in the mid-1720s for performance at the funeral of a patron or governor of the Pietà. The highly original, indeed unique, combination of a muted oboe, a tenor chalumeau and a trio (two soprano instruments and one bass) of viole all’inglese, accompanied by muted strings, lends this work a suitably lugubrious tone, which is only lightened a little when the mutes come off for the fourth movement. The slow opening movement is an adaptation of a sinfonia for a solemn procession to an execution in Vivaldi’s opera Tito Manlio (1719), while the fourth movement borrows the material of the finale of the Concerto without soloist RV123
Discorso di A. Bruers per l'inaugurazione della V settimana. Note e ricerche del Centro di Studi Vivaldiani
Keywords: Goldoni, Carlo -- 1707-1793; Girò, Anna -- 1710-?1748; Ospedale della Pietà (Venice, Italy); 18th Century (1701-1800); Concerto; Venice (Italy)